Environmental outlooks: How they frame futures and long term uncertainty. (September 2016) - Veenman, Sietske; Leroy, Pieter
Highlights: Environmental outlooks frame and thereby create futures. Elaboration of how to assess future framing in outlooks. Environmental outlooks often lack clarity and reflection upon the choices made regarding framing of the environmental problems. Abstract: Futures studies intend to structure our knowledge and our judgement about the future by handling facts and values in a certain way. In other words, futures studies frame futures. These frames might be powerful, triggering social action and societal transformation, yet they risk to be criticised and provoke scepticism. The environmental field has a long tradition in futures studies: environmental outlooks. Some of these outlooks, e.g. those published by the IPCC are among the most prominent examples of outlooks that provoke scientific, social and political debate, create commotion and provoke action. Part of these discussions deal with how outlooks frame the future and how they handle the uncertainty inevitably linked to framing futures. The way these challenges are dealt with may affect the overall assessment of an environmental outlook. This article attempts to identify the way environmental outlooks frame futures. We do not strive for exhaustiveness, but deliberately restrict to an in-depth analysis of a handful of recent environmental outlooks. We conclude that environmental outlooks reflect a lack of clarity and argumentation upon how they frame futures and how they deal with uncertainty. This epistemological and methodological ambiguity risk to affect the outlooks' credibility and impact.